Annual brown shrimp (Crangon crangon) biomass production in Northwestern Europe contrasted to annual landings. (31st July 2016) - Tulp, Ingrid; Chen, Chun; Haslob, Holger; Schulte, Katharina; Siegel, Volker; Steenbergen, Josien; Temming, Axel; Hufnagl, Marc
Abstract : The brown shrimp ( Crangon crangon ) fishery is economically one of the most important fisheries in the North Sea. Fishing is unregulated, apart from the number of licenses and technical measures. The fishery has long been considered sustainable in terms of the effect on the target species, even though annual stocks are not regularly assessed. Average landings constantly increased annually and since 2000 have been 40% higher than in the 1980s and 1990s. Because brown shrimp lack a clear age structure and reproduce almost year-round, an age-based stock assessment is not possible. In the absence of a formal estimate of stock size, it is difficult to judge whether current fishing practices can still be considered sustainable. Here, we use annual survey data collected during peak occurrence in late summer to obtain a depth- and area-stratified, swept-area estimate for the period 1970–2015. The resulting estimate of the total commercial-size shrimp biomass varied between 4000 and 21 000 tonnes over the years. Both parametric and non-parametric methods arrived at very similar results. In combination with length-based mortality estimates (as a proxy for production/biomass ratio), knowledge on the seasonal occurrence, catchability, gear efficiency, and their variation, total adult annual biomass production was estimated. Values ranged between 38 000 and 216 000 tonnes and overlapped at the lower end with total annual commercial landings, which varied between 8000 and 38 500 tonnes, indicating that in some years (1977, 1998, 2007), the larger part of the total brown shrimp production was harvested. Annual brown shrimp landings have gradually increased since the series started, whereas no trend in standing biomass and production was detected. Concurrent with the increase in landings, natural mortality of shrimp by predation has diminished. Considering the increase in fishing pressure and unknown consequence if natural predators recover or shrimp recruitment decreases, the lack of management for the brown shrimp fishery needs to be reconsidered.